2010
DOI: 10.1007/s12306-010-0062-y
|View full text |Cite
|
Sign up to set email alerts
|

The acute bipolar radial head replacement for isolated unreconstructable fractures of the radial head

Abstract: For the acute treatment of radial head fractures, radial head arthroplasty can be considered if open reduction and internal fixation is not technically possible and if simple radial head resection is contraindicated. We report our experience with a bipolar Judet radial head prosthesis. After a mean follow-up of 41.7 months, 16 patients were assessed following radial head replacement. The outcome was assessed clinically, functionally, and radiographically. Outcome was satisfactory in 87.5% of cases. The mean po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 27 publications
(26 reference statements)
2
18
0
Order By: Relevance
“…As such, most of these studies reported only short-to medium-term followup. Most of the studies were carried out in Europe [13,[17][18][19][20][21][22][23][24][25]35,36,[43][44][45][46][47][48][49][50] [21] (4.76%). The radial head implants varied in design with respect to their modularity and component mobility.…”
Section: Literature Search and Study Characteristicsmentioning
confidence: 99%
See 4 more Smart Citations
“…As such, most of these studies reported only short-to medium-term followup. Most of the studies were carried out in Europe [13,[17][18][19][20][21][22][23][24][25]35,36,[43][44][45][46][47][48][49][50] [21] (4.76%). The radial head implants varied in design with respect to their modularity and component mobility.…”
Section: Literature Search and Study Characteristicsmentioning
confidence: 99%
“…There were a few direct injuries to the elbow (7.6%) and only two cases (0.8%) of sports-related injuries. The dominant hand was involved in 54.3% of participants in 13 [21,34,[43][44][45][46]48,49,[51][52][53][54][55]57,58] studies that reported hand dominance.…”
Section: Literature Search and Study Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations